A performance score of the quality of inpatient diabetes care is a marker of clinical outcomes and suggests a cause‐effect relationship between hypoglycaemia and the risk of in‐hospital mortality. Issue 8 (25th June 2020) - Dei Cas, Alessandra; Aldigeri, Raffaella; Ridolfi, Valentina; Vazzana, Angela; Ciardullo, Anna Vittoria; Manicardi, Valeria; Sforza, Alessandra; Tomasi, Franco; Zavaroni, Donatella; Zavaroni, Ivana; Bonadonna, Riccardo C.
Abstract: Aims: To build a tool to assess the management of inpatients with diabetes mellitus and to investigate its relationship, if any, with clinical outcomes. Materials and methods: A total of 678 patients from different settings, Internal Medicine (IMU, n = 255), General Surgery (GSU, n = 230) and Intensive Care (ICU, n = 193) Units, were enrolled. A work‐flow of clinical care of diabetes was created according to guidelines. The workflow was divided into five different domains: (a) initial assessment; (b) glucose monitoring; (c) medical therapy; (d) consultancies; (e) discharge. Each domain was assessed by a performance score (PS), computed as the sum of the scores achieved in a set of indicators of clinical appropriateness, management and patient empowerment. Appropriate glucose goals were included as intermediate phenotypes. Clinical outcomes included: hypoglycaemia, survival rate and clinical conditions at discharge. Results: The total PS and those of initial assessment and glucose monitoring were significantly lower in GSU with respect to IMU and ICU ( P  < .0001). The glucose monitoring PS was associated with lower risk of hypoglycaemia (OR = 0.55; P  < .0001), whereas both the PSs of glucose monitoring and medical therapy resulted associated with higher in‐hospital survival only in the IMU ward (OR = 6.67 P = .001 and OR = 2.38 P = .03, respectively). Instrumental variable analysis with the aid of PS of glucose monitoring showed that hypoglycaemia may play a causal role in in‐hospital mortality ( P = .04). Conclusions: The quality of in‐hospital care of diabetes may affect patient outcomes, including glucose control and the risk of hypoglycaemia, and through the latter it may influence the risk of in‐hospital mortality.